Benign Diseases Masquerading as Cholangiocarcinoma: Can we Differentiate before Surgery? - Wannasri, Thitiporn; Luvira, Vor; Wongwattanachai, Arada; Titapun, Attapol; Srisuk, Tharatip; Kamsa-ard, Supot; Tipwaratorn, Theerawee; Theeragul, Suapa; Pugkhem, Ake; Jarearnrat, Apiwat; et al. (Asian Pacific Journal of Cancer Care, 2022)
Background: Cholangiocarcinoma (CCA) is a potentially lethal disease that requires surgical treatment. There are many benign conditions, those that do not require surgical treatment, displaying imaging characteristics that resemble CCA, leading to therapeutic misadventures. This study aimed to evaluate the proportion of benign conditions that underwent hepatic resection for presumed CCA, and explore the differences between the characteristics of these two entities stratified by primary imaging features of the lesions. Methods: This retrospective study ran between January 2004 and December 2011. We reviewed the pathological records of all 1,402 patients who underwent curative-intent hepatic resection for preoperatively diagnosed CCA. All clinical and pathological parameters were analyzed. Results: The proportion of benign conditions that underwent hepatic resection was 3.78% (53/1,402). For mass-forming lesions, CCA was associated with higher age, alkaline phosphatase, tumor markers, neutrophil to lymphocyte ratio, and mass size. The patients with mass-forming benign conditions were more associated with diabetes mellitus. For lesions with bile duct dilatation, intraductal tumor, including CCA, had higher CA19-9 level and NLR with statistical significance. For cystic lesions, biliary cystic neoplasm had statistical significance in the rate of abdominal pain. Conclusions: The proportion of hepatic resection for benign conditions was quite low. There were many characteristic differences used to differentiate benign mass-forming conditions from CCA, whereas only few markers in the setting of cystic lesions and biliary dilatation. We recommend performing standard hepatic resection in every case, regardless of the type of imaging features, if the lesion has a chance of being CCA.